(untitled) (Journal of Bangladesh Institute of Planners, 2020)
Agriculture plays a foremost role in the stability and progression of the economy of Bangladesh and more than 3/4 of the total population in rural areas derive their livelihood from the agricultural sector (Hossain et.all, 2018, p.1-218). Densely populated country Bangladesh is facing a massive challenge to meet up the food demand of her ever-increasing population. Bangladesh is also a country having nearby sixty-eight thousand villages (banglapedia 2014). The overall economy and national development largely depend on the villages. Most of the villagers are engaged in agriculture and it is an important source of the rural economy. This sector has also a significant combination in the national economy of the country. GDP From Agriculture in Bangladesh increased to 10739.10 BDT Million in 2019 from 10468.80 BDT Million in 2018 (tradingeconomics, 2019). For the overall economic sustainability and growth, it is necessary to improvise the agricultural sector. The study pinpoints the problems of the agriculture sector in Bangladesh and provides some recommendations based on the analysis of the existing agriculture sector in the light of various agricultural plans, policies, and strategies for the sustainable development of the agricultural sector. JBIP, Vol. 13, 2020 (Printed in June 2021), pp. 121-138